ELFA and IFAT Techniques to Detect Chlamydial Infections in Baghdad Women and Its Effect on the Immunoglobulins Level. - Al-Husseinei, Raad K.; Kadaem, Khamael M.; AL-Janabi, Lamya A.; Fathei, Mun’im M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Chlamydia trachomatis is one of the most common human pathogens and considered as one of the causative agents of STDs. This organism cause acute and recurrent pelvic infections and infertility. Patients and Methods: Two hundred and seventy three females were included in the present study, attending infertility department, AL-Elwiya hospital, AL-Jarah private hospital, central public health laboratory and STDs clinic to whom IFAT, ELAF and immunoglobulins concentration were done. Results: Females were divided into three age groups <20; 20-39 and ≥40 years. Single and repeated abortions were 44.9%, 55.1% respectively. Primary and secondary infertility were 55.6% and 44.4%. Higher abortions rate were in the age group 20-39 years which represents 31.5% and 41.6% in single and repeated abortions. Primary and secondary infertility were high in the same age group which represents 42.6% and 33.3% of the total investigated females, also the multipartners within the same age group constitutes 56.7%.Chlamydial infections detected by IFAT technique constitute 12.8% which were represented as 14.6%, 11.1%, 36.7% and 5% in abortions, infertility, multipartners and fertility with no abortion groups respectively. While by ELFA technique the percentages were 12.4%, 9.3%, 30% and 4% in the same mentioned groups.Immunoglobulins mean value in females with chlamydial infections wee as follows IgG = 2102.1 mg/dl; IgA = 317.9 mg/dl and IgM = 272.5 mg/dl. Which were more than the normal values of the immunoglobulins. Conclusions: Chlamydial infections were distributed largely among multipartners than other aborted females. High abortions were noted in age group 20-39 years. IFAT technique was more reliable than ELFA technique to detect chlamydial infections. IgG and IgM concentrations were higher than normal concentrations, while IgA remains normal.